Identification of Physics Concepts in the Local Wisdom of Cowek Pottery Making in Gedangan, Lamongan - Azizatul Nur Rohmah; Adrian Bagas Damarsha; Kifle Kassaw Mulatu; Oka Saputra (Prodi S2 Pendidikan Fisika Universitas Negeri Surabaya, 2026)
Cultural heritage is an important part of shaping community identity because it reflects history, values, and unique ways of life. One example is the craft of cowek pottery. However, globalization has caused communities to slowly abandon local cultural values. Therefore, preserving local wisdom is necessary, one of which can be done through integration into school learning. Physics education has great potential to promote local wisdom because many physics concepts are directly related to traditional practices. This study aims to explore the physics concepts found in the process of making cowek pottery in Gedangan Village, Lamongan, and identify their potential as sources of contextual learning. The research uses a qualitative descriptive method with an ethnographic approach, involving two cowek craftsmen selected through purposive sampling. Data were collected through observation, interviews, documentation, and literature study. Data analysis employed the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The study results show that each stage of cowek production involves physical concepts such as plasticity, pressure, friction, centripetal force, work and energy, changes in form, and heat transfer. The cowek making process also presents various physical phenomena that can help students understand concepts more concretely and meaningfully, making it highly potential as a contextual learning resource. These findings confirm that traditional activities are closely linked with the application of physics laws. Thus, local wisdom in cowek making can be utilized as a relevant and actual learning resource to support students’ understanding of physics concepts in everyday life.